The Urgency of Regulation of Tax Criminal Actions in Preventing Loss of State Revenue in the Tax Sector - Mushafi; M. Arief Amrullah; Y.A. Triana Ohoiwutun; Aan Efendi (PT Inovasi Pratama Internasional, 2023)
This article examines the urgency of regulating tax crimes in preventing loss of state revenue in the tax sector. The research method used in writing this article is a normative juridical paradigm or doctrinal legal research. The basis for writing this article is literature with a focus on analyzing primary legal materials and secondary legal materials. That is, this research will refer to the legal norms contained in the laws and regulations related to criminal law legislation policies in the tax sector. The results of this study are that the regulation of tax crimes has an important role in preventing or overcoming the occurrence of fraud and crime in the field of taxation. In addition, the regulation of tax crimes as an effort to overcome crime in the tax sector can be carried out preventively and repressively so that the state avoids losses to income in the tax sector. Keywords; Regulations, Crimes, Taxes, Losses, State Income